Pomegranate Supplementation Accelerates Recovery of Muscle Damage and Soreness and Inflammatory Markers after a Weightlifting Training Session - Ammar, Achraf; Turki, Mouna; Chtourou, Hamdi; Hammouda, Omar; Trabelsi, Khaled; Kallel, Choumous; Abdelkarim, Osama; Hoekelmann, Anita; Bouaziz, Mohamed; Ayadi, Fatma; Driss, Tarak; Souissi, Nizar (PLOS ONE, 2016)
Purpose The aim of this study was to investigate the effect of natural Pomegranate juice supplementation on performance and acute and delayed responses of muscle soreness and biomarkers of muscle damage after a weightlifting training session. Methods Nine elite weightlifters (21±0.5 years) performed two Olympic-Weightlifting-sessions after either placebo (PLA) or natural pomegranate juice (POMj) supplementations. Heart rate, blood pressure and blood samples (hematological parameters, muscle damage and C-reactive protein (CRP)) were collected at rest, 3min and 48h after each session. Weightlifting performance, RPE, and DOMS were also assessed after each training session. Results T-test showed higher performance (+8.30%) and lower RPE values (-4.37%) using POMj supplementation (p<0.05) in comparison with PLA. For the DOMS values, a significant improvement (13.4%) was shown only for the knee extensors (p<0.01) using the POMj. Compared to PLA condition, POMj attenuated the acute (i.e., 3min) increase of systolic blood pressure (SBP), HR, CK and LDH (p<0.05; -4.46%, -1.81%, -8.75%, -1.64%, respectively) and blunted the significant increase of ASAT, PAL and CRP (p>0.05). Additionally, during the 48h following the training session, POMj improved the recovery kinetic of SBP (p<0.01, 7.97%), CK (p<0.001, 11.34%), LDH (p<0.05, 7.30%) and ASAT (p<0.05, 6.77%). Indeed, the present study showed that 48h of recovery associated to natural POMj supplementation was sufficient to reach the resting values of the selected muscle damage markers after intensive training session. Conclusion Natural POMj seems to ameliorate the capacity to adhere to an intensive training program. Therefore, elite weightlifters are advised to use natural POMj during intensive training program and competition to accelerate muscle recovery. Trial Registration ClinicalTrials.gov NCT02697903